2011
DOI: 10.1159/000324441
|View full text |Cite
|
Sign up to set email alerts
|

The Total Face Mask Is More Comfortable than the Oronasal Mask in Noninvasive Ventilation but Is Not Associated with Improved Outcome

Abstract: Background: Noninvasive positive-pressure ventilation (NPPV) is commonly used to improve ventilation and oxygenation and avoid endotracheal intubation and mechanical ventilation. Although clinically indicated, most patients fail to use NPPV due to mask intolerance. A total face mask was designed to increase compliance, but whether this translates into better outcome (improvement in clinical and blood gas parameters and less intubation) is unknown. Objectives: We compared the evolution of the clinical parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 42 publications
1
17
1
3
Order By: Relevance
“…Nevertheless, 23 (64%) out of 36 patients in whom FM-NIV failed to reverse ARF and, therefore, switched to total FM survived hospital discharge. Patients of the "FM failure" group, compared to those of the "FM success" group, required longer time of NIV during the first 48 hrs (40 [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] hrs vs. 22 [15][16][17][18][19][20][21][22][23][24][25][26][27][28] hrs; p < 0.001, respectively) and a longer stay in critical care setting (8 [5-0] days vs. 5 [3][4][5][6][7][8] days; p = 0.007, respectively), and needed higher inspiratory positive airway pressure levels (18 [16][17][18][19][20] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, 23 (64%) out of 36 patients in whom FM-NIV failed to reverse ARF and, therefore, switched to total FM survived hospital discharge. Patients of the "FM failure" group, compared to those of the "FM success" group, required longer time of NIV during the first 48 hrs (40 [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] hrs vs. 22 [15][16][17][18][19][20][21][22][23][24][25][26][27][28] hrs; p < 0.001, respectively) and a longer stay in critical care setting (8 [5-0] days vs. 5 [3][4][5][6][7][8] days; p = 0.007, respectively), and needed higher inspiratory positive airway pressure levels (18 [16][17][18][19][20] …”
Section: Resultsmentioning
confidence: 99%
“…Three randomized studies have been conducted to compare the former model of total FM (Total Face, Respironics, Murrysville, PA) to conventional facial masks as the initial interface strategy for NIV in patients in ARF (32)(33)(34). Total face was found more comfortable only in patients with prolonged ARF (32,33), but its use was not associated with reduction in intubation rate or mortality (32,34). It is noteworthy that its ability to prevent facial pressure sores has never been tested, especially in patients for whom NIV had to be continued over long periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…In subjects with acute respiratory failure, Ozsancak et al 125 found that the oronasal mask and total face mask were perceived to be equally comfort- able and had similar application times. In another study of subjects with acute respiratory failure, Chacur et al 126 reported that the total face mask was more comfortable than the oronasal mask and suggested that the total face mask should be available as an option in units where NIV is routinely applied. In a normal volunteer study, Holanda et al 127 found that the total face mask avoided pain on the bridge of the nose and presented no air leaks around the eyes and mouth.…”
Section: Technical Aspects Which Interface?mentioning
confidence: 99%
“…NIV delivered via TFM has been proposed as an intervention to reverse ARF, and its use has been associated with better tolerance and comfort compared with an ONM. [33][34][35] These findings reinforce the importance of recommending the use of interfaces that generate less pressure against the face (ie, TFM or helmet) 36 for subjects who need prolonged NIV to prevent the development of SB, increasing the compliance and success of NIV. Furthermore, in patients who require prolonged intermittent mandatory ventilation, rotating the use of different types of masks may be another strategy for decreas- Hosmer-Lemeshow test ϭ chi-square ϭ 0.016.…”
Section: Discussionmentioning
confidence: 60%